Cornell note-taking strategy instruction for Gen Z: enhancing EFL students’ reading comprehension - Ji-Young Seo (Asian-Pacific Journal of Second and Foreign Language Education)
Abstract In this technological and AI era, Generation Z spends more time reading texts on technological devices, prefers bullet points over lengthy, complex material (Bano et al., in JEED 5 42–59, 2018), and is increasingly dependent on AI-driven tools, which has made them more reluctant to read independently. The Cornell note-taking method encourages students to organize information, generate questions, and summarize ideas using their own words, helping them develop their metacognitive abilities and critical thinking. Therefore, this study examines the extent to which the Cornell note-taking method improves the reading comprehension of Gen Z students when engaging with longer academic texts. Seventy-seven students divided into two groups participated in the 15-week study: a Cornell note group and a Personal note group. Two reading comprehension tests were administered, and a repeated measures two-way ANOVA was conducted to identify whether there were any statistically significant differences in the two groups’ test scores. A questionnaire was also administered at the end of the intervention to assess their perceptions of the Cornell note-taking method. The results revealed that the Cornell note-taking group outperformed the personal note-taking group, with a significant difference in test scores over time. A significant interaction effect was also observed between time and group. The Cornell note-taking group also exhibited higher confidence in class engagement and better retention of English content and expressions, which benefited their exam preparation. A majority also held positive attitudes toward using this method in the future. The findings highlight the value of teaching reading using the Cornell note-taking strategy.